2023
DOI: 10.1038/s44159-023-00207-7
|View full text |Cite|
|
Sign up to set email alerts
|

The cognitive challenges of cooperation in human and nonhuman animals

Abstract: Cooperation is widespread in nature, occurring in every taxa on Earth. Nevertheless, the contexts in which cooperation occursand the forms it takesvary widely. In this Review, we outline how cooperation can evolve in nature and the cognition needed to support cooperation in different scenarios. We argue that the cognitively simplest forms of cooperation are those where an organism does not need to individually recognise interaction partners and that do not depend upon individuals keeping track of their partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 203 publications
0
3
0
Order By: Relevance
“…Our model demonstrated that more cooperative individuals can evolve to show higher plasticity compared to less cooperative individuals, even under very simple behavioural and evolutionary rules. This suggests that the behaviour that we observed in this experiment can arise via simple evolutionary processes, and does not rely on high levels of cognition that other mechanisms of assortment might rely on (e.g., reputational book-keeping (35)). We also found that the relative cost incurred when nobody cooperates affected the strength of the relationship between cooperation and plasticity, suggesting that ecological factors could be important in the relationship between these traits.…”
Section: Discussionmentioning
confidence: 65%
“…Our model demonstrated that more cooperative individuals can evolve to show higher plasticity compared to less cooperative individuals, even under very simple behavioural and evolutionary rules. This suggests that the behaviour that we observed in this experiment can arise via simple evolutionary processes, and does not rely on high levels of cognition that other mechanisms of assortment might rely on (e.g., reputational book-keeping (35)). We also found that the relative cost incurred when nobody cooperates affected the strength of the relationship between cooperation and plasticity, suggesting that ecological factors could be important in the relationship between these traits.…”
Section: Discussionmentioning
confidence: 65%
“…These studies have sparked discussions regarding, for example, the cognitive prerequisites for and affective aspects of cooperation, methodological challenges for empirical research on cooperation and prosociality across taxa, and contextual factors influencing the outcome of experiments on prosociality (e.g. Brosnan et al 2010 ; Cronin 2012 ; Marshall-Pescini et al 2016 ; Massen et al 2019 ; Melis and Raihani 2023 ). However, comparisons across studies and species may be hampered by considerable variation in the underlying concepts and what counts as prosocial behaviour (Pfattheicher et al 2022 ).…”
Section: Towards a Conceptual Framework For Comparative Research Into...mentioning
confidence: 99%
“…Animals in this category not only understand their partner’s role but also form shared representations of the shared goal and have a mutual commitment to achieve it together. This form of collaboration is a hallmark of human cooperation and is demonstrated by children from around 3 years old onward (reviewed in [ 4 , 30 ]).…”
Section: Introductionmentioning
confidence: 99%